A proteome analysis of pig pancreatic islets and exocrine tissue by liquid chromatography with tandem mass spectrometry. Issue 6 (2nd November 2017) - Nakashima, Yoshiki; Miyagi-Shiohira, Chika; Kobayashi, Naoya; Saitoh, Issei; Watanabe, Masami; Noguchi, Hirofumi
ABSTRACT: Liquid chromatography with tandem mass spectrometry (LC-MS/MS) is a proteome analysis method, and the shotgun analysis by LC-MS/MS comprehensively identifies proteins from tissues and cells with high resolving power. In this study, we analyzed the protein expression in pancreatic tissue by LC-MS/MS. Islets isolated from porcine pancreata (purity ≥95%) and exocrine tissue (purity ≥99%) were used in this study. LC-MS/MS showed that 13 proteins were expressed in pancreatic islets only (Group I), 43 proteins were expressed in both islets and exocrine tissue (Group I&E), and 102 proteins were expressed in exocrine tissue only (Group E). Proteins involved in islet differentiation and cell proliferation were identified in Group I (e.g. CLUS, CMGA, MIF). In addition, various functional proteins (e.g. SCG2, TBA1A) were identified in islet by using the new method of 'principal component analysis (PCA)'. However, the function of such proteins on islets remains unclear. EPCAM was identified in Group E. Group E was found to include proteins involved in clinical inflammatory diseases such as pancreatitis (e.g. CBPA1, CGL, CYTB, ISK1 and PA21B). Many of these identified proteins were reported less frequently in previous studies, and HS71B, NEC2, PRAF3 and SCG1 were newly detected in Group I while CPNS1, DPEP1, GANAB, GDIB, GGT1, HSPB1, ICTL, VILI, MUTA, NDKB, PTGR1, UCHL3, VAPB and VINC were newly detected in Group E. These results show that comprehensive expression analysis of proteins by LC-MS/MS is useful as a method to investigate new factors constructing cellular component, biological process, and molecular function.